Naringenin attenuates early hepatocarcinogenesis induced by a MASH model - Linda Vanessa Márquez-Quiroga; Aline Barboza-López; Jose Y. Suárez-Castillo; Irina Cardoso-Lezama; Miguel Á. Fuentes-Figueroa; Eduardo E. Vargas-Pozada; Juan D. Rodriguez-Callejas; Erika Ramos-Tovar; Carolina Piña-Vázquez; Jaime Arellanes-Robledo; Saúl Villa-Treviño; Pablo Muriel (Annals of Hepatology)
Introduction and Objectives: Nucleotide-binding oligomerization domain-like receptor family pyrin domain-containing 3 (NLRP3) inflammasome plays a critical role in the progression of metabolic dysfunction-associated steatohepatitis (MASH). Here, we investigated the effects of naringenin (NAR) on early hepatocellular carcinoma (HCC) experimentally induced in a rat MASH model and whether the NLRP3 inflammasome/pyroptosis pathway was involved. Materials and Methods: The animals were fed a hepatopathogenic diet for 16 weeks and carbon tetrachloride (400 mg/kg, i.p.) and diethylnitrosamine (40 mg/kg, i.p.) were injected once a week. NAR was administered at 100 mg/kg p.o. The effects of NAR on the MASHHCC protocol were evaluated using biochemical, histological, in silico, and molecular biological approaches. Results: NAR significantly mitigated liver damage, as evidenced by the reduction in liver damage markers. It also reduced steatosis and inflammation, as determined by decreased lipid accumulation and sterol regulatory element-binding protein 1C, interleukins 1-beta and 18, and nuclear factor kappa B levels, and also increased peroxisome proliferator-activated receptor gamma levels. NAR inhibits the formation of NLRP3, including the recruitment of caspase-1 and gasdermin D proteins, and reduces the levels of transforming growth factor-beta, alpha-smooth muscle actin, and hepatic collagen 1, thereby diminishing extracellular matrix synthesis. Furthermore, gamma-glutamyl transpeptidase activity, glutathione S-transferase pi 1, and the proliferation marker KI67 were considerably reduced. Conclusions: Our findings show that NAR has the potential to inhibit early HCC induced in the context of MASH, thereby suggesting that NAR could be used for MASH treatment in humans.